Foreword - Lynden Griggs (Legal Education Review)
This article discusses our experience in creating an elective international law course for degree credit at Sydney Law School, the ‘Himalayan Field School: Development, Law and Human Rights’, which is run annually in Nepal with Kathmandu School of Law. The course combines unique, participatory experiential methods with doctrinal and theoretical learning, peer-to-peer learning, and personal critical reflection. The course is inter-disciplinary and cross-cultural, set in a developing country which takes relatively privileged western law students outside of their own habitat. The article first describes the background to the course, including the internationalisation of legal education and Nepal as the case study. It then discusses the course aims; the design of the curriculum content and the teaching and learning methods; assessment types and rationale; and student evaluation and course improvement. It considers aspects of the teaching-research nexus, including a research-led course design, a research-driven curriculum, the use of socio-legal research methods as a learning tool, the promotion of student interest in research, and a research dividend for teaching staff. The final part reflects on the challenges and risks (including the difficult operating environment of a post-conflict developing country), and concludes by addressing critiques of this course.